THE LEGALITY OF REVERSE ENGINEERING AND THE PROTECTION OF TRADE SECRETS IN THE SOFTWARE INDUSTRY - AllahRakha, Naeem (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
This article explores the legality of reverse engineering and the protection of trade secrets in the software industry. The study aims to provide a comprehensive understanding of the legal framework governing these issues and their implications for software developers and companies. Through a qualitative research methodology employing a doctrinal approach, the study examines relevant legal documents and scholarly articles. The findings suggest that while reverse engineering is generally legal, limitations and exceptions exist to protect trade secrets. The study highlights the importance of implementing effective legal and practical measures to safeguard valuable information in the software industry. Recommendations include the use of licensing agreements, confidentiality agreements, and technological protection measures. This research emphasizes the importance of balancing innovation through reverse engineering with the protection of intellectual property rights, while also addressing broader implications for the software industry. This article contributes by providing legal and practical guidance for software developers and companies in navigating the challenges between innovation through reverse engineering and the protection of trade secrets. Artikel ini membahas legalitas rekayasa balik (reverse engineering) dan perlindungan rahasia dagang dalam industri perangkat lunak. Penelitian ini bertujuan memberikan pemahaman yang komprehensif mengenai kerangka hukum yang mengatur isu-isu tersebut serta implikasinya bagi pengembang perangkat lunak dan perusahaan. Melalui metodologi penelitian kualitatif dengan pendekatan doktrinal, penelitian ini menganalisis dokumen hukum yang relevan dan artikel ilmiah. Temuan menunjukkan bahwa meskipun rekayasa balik umumnya legal, terdapat batasan dan pengecualian untuk melindungi rahasia dagang. Penelitian ini menekankan pentingnya penerapan langkah-langkah hukum dan praktis yang efektif untuk melindungi informasi berharga dalam industri perangkat lunak. Rekomendasi mencakup penggunaan perjanjian lisensi, perjanjian kerahasiaan, dan langkah-langkah perlindungan teknologi. Penelitian ini menyoroti pentingnya menyeimbangkan inovasi melalui rekayasa balik dengan perlindungan hak kekayaan intelektual, serta membahas implikasi yang lebih luas bagi industri perangkat lunak. Artikel ini berkontribusi dalam memberikan panduan hukum dan praktis bagi pengembang perangkat lunak dan perusahaan dalam menavigasi tantangan antara inovasi melalui rekayasa balik dan perlindungan rahasia dagang.